Current Trends, Overlooked Issues, and Unmet Challenges in Virtual Screening - Stumpfe, Dagmar; Bajorath, Jürgen (Journal of chemical information and modeling, 2020)
Virtual compound screening focusing on hit identification is among the most popular computational approaches in pharmaceutical research. Yet, its opportunities and limitations are often not fully understood. Herein, we critically discuss several aspects of virtual screening that are thought to be of particular relevance for the field going forward.